Design, synthesis, and evaluation of novel N-(4-phenoxybenzyl)aniline derivatives targeting acetylcholinesterase, β-amyloid aggregation and oxidative stress to treat Alzheimer's disease - Srivastava P.; Tripathi P.N.; Sharma P.; Shrivastava S.K. (My University, 2025)
Novel hybrids N-(4-phenoxybenzyl)aniline were designed, synthesized, and evaluated for their potential AChE inhibitory activity along with antioxidant potential. The inhibitory potential (IC50) of synthesized analogs was evaluated against human cholinesterases (hAChE and hBChE) using Ellman's method. Among all the tested compounds, 42 with trimethoxybenzene substituent showed maximum hAChE inhibition with the competitive type of enzyme inhibition (IC50 = 1.32 µM; Ki = 0.879 µM). Further, parallel artificial membrane permeation assay (PAMPA-BBB) showed favorable BBB permeability by most of the synthesized compounds. Meanwhile, compound 42 also inhibited AChE-induced Aβ aggregation (39.5–66.9%) in thioflavin T assay. The in vivo behavioral studies showed dose-dependent improvement in learning and memory by compound 42. The ex vivo studies also affirmed the significant AChE inhibition and antioxidant potential of compound 42 in brain homogenates. © 2019 Elsevier Ltd